Revenue effects of participation in smallholder organic cocoa production in tropical Africa: A case study - Peter Gibbon; Yumiao Lin; Sam Jones (Danish Institute for International Studies (DIIS), 2009)
This paper examines the revenue effects of certified organic contract farming and of use of organic farming methods in a tropical African context. These are compared with 'organic by default' conventional farming systems without contractual relations. Survey data from a medium-size cocoa-vanilla contract farming scheme in Uganda is reported using a standard OLS regression and propensity score matching approaches. The analysis finds that there are positive revenue effects for the certified crops from both participation and, more modestly, from using organic farming techniques.
Keywords: 330; Ökologischer Landbau; Vertragsanbau; Kakaoanbau; Gewürz; Uganda